Solid composition containing amorphous poorly water-soluble material and method for producing same
By heating and stirring the ammonia material, HPMC and polysaccharide, forming a solid composition with low XRD analysis value, solving the problem of difficulty in producing new water-soluble ammonia material in the prior art, achieving high crystallinity and long-term stability, and providing a method to accurately determine the proportion of the material.
Patent Information
- Application Number
- JP2020203049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-13
- Filing Date
- 2020-12-07
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-08-28
AI Technical Summary
It is difficult to effectively produce novel aquamarine-soluble ammonia-shaped materials and solid compositions thereof in the prior art, and it is difficult to accurately determine the ratio of crystalline and crystalless substances in these materials.
The solid composition with low XRD analysis values was formed by heating and stirring the ammonia material, hydroxypropylmethyl ether cellulose (HPMC) and other polysaccharides with the ammonia material, and the ratio of crystalline and crystalless substances in the material was determined using powder X-ray diffraction (XRD) analysis and calibration curves.
The production of a new water-soluble ammonia-shaped material with high crystallinity and long-term stability is achieved, and methods for evaluating and controlling the quality of the composition are provided.
Smart Images

Figure 0007663347000018 
Figure 0007663347000019 
Figure 0007663347000020
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a solid composition containing an amorphous poorly water-soluble material, and a method for producing the same, etc. The present disclosure also relates to a method for determining the proportion of crystalline and / or amorphous matter in the poorly water-soluble material contained in the solid composition.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to Japanese Patent Application Nos. 2019-159126 and 2020-22821, filed in Japan on August 30, 2019 and February 13, 2020, respectively, the entire contents of which are hereby incorporated by reference into this disclosure. [Background technology]
[0003] 2. Description of the Related Art Conventionally, techniques for amorphizing poorly water-soluble materials have been known for the purpose of increasing the water solubility or bioabsorbability of the poorly water-soluble materials. For example, there have been proposed a method of forming a complex of curcumin and / or its analogue with a water-soluble cellulose derivative using an organic solvent method having a step of dissolving in a water-organic solvent mixed solution (Patent Document 1); a method of mixing (A) poorly soluble polyphenols, (B) at least one selected from plant-derived polysaccharides, seaweed-derived polysaccharides, microbial-derived polysaccharides, plant-derived polypeptides, and microbial-derived polypeptides, and (C) at least one selected from monosaccharides and disaccharides, followed by heating and melting the mixture and cooling and solidifying the melt (Patent Document 2); a method of heating and kneading a crystalline poorly water-soluble polyphenol, a hydrophilic polymer, and a nonionic surfactant (Patent Documents 3 and 4); and a method of melting crystalline curcumin alone to make it amorphous, followed by adding a water-soluble polymer such as dextrin (Patent Document 5). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2015 / 174475 Brochure [Patent Document 2] JP 2016-049105 A [Patent Document 3] WO2017 / 061627 Brochure [Patent Document 4] JP 2019-123700 A [Patent Document 5] WO2019 / 160146 Brochure Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is a demand for providing a new solid composition containing an amorphous, poorly water-soluble material and a method for producing the same. An object of the present disclosure is to provide a new solid composition containing an amorphous, poorly water-soluble material, and a method for producing the same. Another object of the present disclosure is to provide a method for easily determining the proportion of crystalline and / or amorphous matter in the poorly water-soluble material contained in the solid composition. [Means for solving the problem]
[0006] The present disclosure includes the following aspects. [1] A solid composition containing an amorphous, poorly water-soluble material [1-1] Amorphous poorly water-soluble material (1a), Hydroxypropyl methylcellulose (hereinafter referred to as "HPMC") (2), and Polysaccharides with 5 or more sugars other than HPMC (3) A solid composition comprising: A solid composition, wherein the XRD analysis of said solid composition is 4.0% or less: In addition, the XRD analysis value here is a value calculated by the formula: {(S2) / ((S1)+(S2))}×100(%), where (S1) is the area of the halo peak in the range of 2θ=5 to 60° in a chart obtained by analyzing the solid composition with a powder X-ray diffractometer, and (S2) is the area of the sharp peak originating from the crystalline water-insoluble material (1b) that exceeds the halo peak (the same applies hereinafter). [1-2] The solid composition according to [1-1], wherein the amorphous poorly water-soluble material (1a) is at least one selected from the group consisting of polyphenols, polyphenol derivatives, carotenoids, coenzyme Q10, vitamins, and sesamin. [1-3] The polyphenol is at least one selected from the group consisting of curcumin, luteolin, silymarin, rutin, quercetin, myricitrin, quercitrin, isoquercitrin, naringenin, resveratrol, and hesperetin; The polyphenol derivative is a polymethoxyflavonoid, The carotenoid is at least one selected from the group consisting of xanthophylls, carotenes, and apocarotenoids; The vitamin is at least one selected from the group consisting of vitamin A, vitamin D, vitamin E, and vitamin K. The solid composition according to [1-2]. [1-4] The solid composition according to at least one of [1-1] to [1-3], wherein the polysaccharide (3) is selected from the group consisting of gum arabic, hydroxypropyl cellulose (HPC), gum ghatti, low molecular weight gum ghatti, modified starch, locust bean gum, guar gum, alginic acid, salts of alginic acid, carrageenan, pectin, xanthan gum, pullulan, microcrystalline cellulose, fermented cellulose, methylcellulose, carboxymethylcellulose (CMC), dextrin (including resistant dextrin), cyclodextrin (including α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin), soybean polysaccharides, agar, tamarind seed gum, guar gum hydrolyzate, karaya gum, tara gum, welan gum, and gellan gum. [1-5] The solid composition according to [1-4], wherein the polysaccharide (3) is a combination of hydroxypropyl cellulose (HPC) and another polysaccharide. [1-6] The solid composition according to [1-5], wherein the other polysaccharide is gum arabic. [1-7] The solid composition according to any one of [1-1] to [1-6], wherein the XRD analysis value is 1.0% or less. [1-8] A solid composition, comprising the solid composition according to any one of [1-1] to [1-7], and a crystalline poorly water-soluble material (1b) added thereto.
[0007] [2] Uses of solid compositions [2-1] An oral composition comprising the solid composition according to any one of the above [1-1] to [1-8]. [2-2] A pharmaceutical, a quasi-drug, a food or beverage, an oral care product, or a cosmetic comprising the solid composition according to any one of the above [1-1] to [1-8] together with an additive for the pharmaceutical, the quasi-drug, the food or beverage, the oral care product, or the cosmetic.
[0008] [3] Method for producing a solid composition containing an amorphous poorly water-soluble material [3-1] A method for producing the solid composition according to any one of the above [1-1] to [1-8], comprising a step of heating and kneading a crystalline poorly water-soluble material (1b), HPMC (2), and a polysaccharide having 5 or more sugars other than HPMC (3) using a kneader. [3-2] The method according to [3-1] above, wherein the crystalline poorly water-soluble material (1b) is at least one selected from the group consisting of polyphenols, polyphenol derivatives, carotenoids, coenzyme Q10, vitamins, and sesamin. [3-3] The production method according to [3-1] or [3-2] above, wherein the heat-kneading step is carried out at a temperature equal to or higher than the glass transition temperature Tg of the crystalline poorly water-soluble material (1b). [3-4] The production method according to any one of [3-1] to [3-3] above, further comprising at least one step selected from the group consisting of a cooling step, a crushing or pulverizing step, a drying step, a granulation step, and a sizing step.
[0009] [4] Method for calculating the proportion of crystalline and / or amorphous matter in a poorly water-soluble material [4-1] A method for calculating the proportion of crystalline matter (1b) and / or amorphous matter (1a) contained in a poorly water-soluble material (1) in a solid composition (measurement sample) containing a poorly water-soluble material (1), HPMC (2), and a polysaccharide (3) other than HPMC having 5 or more sugars, comprising: The process is as follows: (A) determining the XRD analysis value of a measurement sample; and (B) A step of applying the XRD analysis value of (A) to a calibration curve prepared in advance to calculate the proportion of crystalline (1b) and / or amorphous (1a) in the poorly water-soluble material contained in the measurement sample; Including, The calibration curve is prepared by obtaining XRD analysis values of standard samples containing various proportions of the crystalline poorly water-soluble material (1b) for each standard sample, plotting the proportion (%; theoretical value) of the crystalline (1b) in the standard sample or in the poorly water-soluble material contained in the standard sample on the X-axis and the XRD analysis values on the Y-axis. The calculation method. [4-2] The calculation method described in [4-1], wherein the standard sample is two or more solid compositions containing a water-insoluble material (1) containing crystalline and amorphous water-insoluble materials in a predetermined ratio, HPMC (2), and a polysaccharide other than HPMC having five or more sugars (3). [4-3] A method for evaluating or controlling the quality of a solid composition by calculating the proportion of crystalline and / or amorphous matter in a poorly water-soluble material contained in the solid composition using the method described in [4-1] or [4-2]. Effect of the Invention
[0010] According to the present disclosure, there are provided a solid composition containing a new amorphous poorly water-soluble material having high amorphousness and long-term stability, and a method for producing the same, etc. Furthermore, according to the present disclosure, for a solid composition containing crystalline and amorphous poorly water-soluble materials, the proportion (content) of crystalline and / or amorphous material contained in the poorly water-soluble material can be calculated, and this can be used for evaluating or managing the quality of the solid composition. [Brief description of the drawings]
[0011] [Figure 1-1]The materials of the solid compositions (Examples 1 to 4 and Example 1') produced in Test Example 1 and the evaluation results of the solid compositions are shown. Specifically, the residual content rate (%) of the poorly water-soluble material (curcumin), the evaluation results of the amorphous nature of the poorly water-soluble material (X-ray powder diffraction (XRD) analysis chart, degree of amorphousness [XRD analysis value / evaluation]), and the evaluation results of the change in appearance after storage are shown. In the figures, the X-axis of the XRD analysis chart indicates 2θ (°), and measurements were performed at 2θ = 5° to 60°. Since no peaks were observed in the range of 2θ = 40° to 60°, only the range of 2θ = 5° to 40° is shown in the following Figures 1-2 to 7-1. The Y-axis of the XRD analysis chart indicates signal intensity, and indicates 0 to 5000 Counts (same for Figures 1-2 to 4-4 and Figure 6). In the figures, the "XRD analysis value" indicated with * means the value calculated by {(S2) / ((S1)+(S2))}×100 (same for Figures 2-1 to 7-1). In the figures, the storage conditions indicated with ** are "40°C, 75% relative humidity for one month" (same for Figures 1-2 to 4-4. However, the poorly water-soluble materials tested with different storage periods are described below). [Figure 1-2] The materials of the solid compositions (Comparative Examples 1 to 5) produced in Test Example 1 and the evaluation results of the solid compositions are shown. [Figure 2-1] The materials of the solid compositions (Examples 5 to 8) produced in Test Example 2 and the evaluation results of the solid compositions are shown. [Figure 2-2] The materials of the solid compositions (Examples 9 to 12) produced in Test Example 2 and the evaluation results of the solid compositions are shown. [Figure 3-1] The materials of the solid compositions (Examples 13 to 16) produced in Test Example 3 and the evaluation results of the solid compositions are shown. [Figure 3-2] The materials of the solid compositions (Examples 17 to 20) produced in Test Example 3 and the evaluation results of the solid compositions are shown below. [Figure 3-3] The materials of the solid compositions (Examples 21 to 24) produced in Test Example 3 and the evaluation results of the solid compositions are shown below. [Diagram 3-4] The materials of the solid compositions (Examples 25 to 28) produced in Test Example 3 and the evaluation results of the solid compositions are shown below. [Figure 3-5]The materials of the solid compositions produced in Test Example 3 (Examples 29 to 32) and the evaluation results of the solid compositions are shown below. [Diagram 3-6] The materials of the solid compositions produced in Test Example 3 (Examples 33 to 36) and the evaluation results of the solid compositions are shown below. [Diagram 3-7] The materials of the solid compositions produced in Test Example 3 (Examples 37 to 38) and the evaluation results of the solid compositions are shown below. [Figure 4-1] The materials of the solid compositions produced in Test Example 4 (Examples 39 to 42) and the evaluation results of the solid compositions are shown below. [Figure 4-2] The following shows the materials of the solid compositions (Examples 43 to 45) produced in Test Example 4, and the evaluation results of the solid compositions. **: Example 43 only, after storage for 2 weeks. [Figure 4-3] The following shows the materials of the solid compositions (Examples 46 to 48) produced in Test Example 4, and the evaluation results of the solid compositions. **: Example 46 only, after storage for 2 weeks. [Figure 4-4] The following shows the materials of the solid compositions (Examples 49 to 50, Comparative Example 6) produced in Test Example 4, and the evaluation results of the solid compositions. **: Example 50 and Comparative Example 6, after storage for 2 weeks. [Diagram 5] The materials of the solid compositions (Comparative Examples 7 and 8) produced by the organic solvent method in Test Example 5 and the evaluation results of the obtained solid compositions are shown below. [Figure 6] The materials of the solid compositions produced in Test Example 6 (Comparative Examples 9 to 12) and the evaluation results of the obtained solid compositions are shown below. [Figure 7-1] The materials of the powder mixtures (test samples 1 to 5) produced in Test Example 7 and the XRD analysis results (XRD analysis charts and XRD analysis values) of the obtained powder mixtures are shown. [Figure 7-2] A calibration curve is shown in which the proportion of crystalline curcumin (% crystalline CUR content in the powder mixture) in the powder mixture (test samples 1 to 5) shown in Figure 7-1 is plotted on the X-axis and the XRD analysis values obtained for the powder mixture are plotted on the Y-axis. [Figure 7-3]A calibration curve is shown in which the proportion of crystalline curcumin in the total curcumin (CUR) contained in the powder mixtures (test samples 1 to 5) shown in Figure 7-1 (crystalline CUR content as a percentage of the total CUR content) is plotted on the X-axis and the XRD analysis values obtained for the powder mixtures are plotted on the Y-axis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] term The symbols and abbreviations in this specification can be understood as meanings commonly used in the technical field to which the present invention belongs, in accordance with the context of this specification, unless otherwise limited. In this specification, the phrase "comprises" is used with the intention of including the meaning of the phrase "consisting essentially of" and the meaning of the phrase "consisting of". Unless otherwise limited, the steps, treatments, or operations described in this specification can be carried out at room temperature. In this specification, room temperature can mean a temperature in the range of 10 to 40°C.
[0013] <Solid composition containing amorphous poorly water-soluble material (1a)> The solid composition according to one embodiment of the present disclosure (hereinafter also referred to as the present solid composition) comprises: Amorphous poorly water-soluble material (1a), Hydroxypropyl methylcellulose (HPMC) (2), and Contains polysaccharides other than HPMC (3).
[0014] 1. Poorly water-soluble materials (1) Hereinafter, in this specification, an amorphous poorly water-soluble material will be referred to as "amorphous (1a)" or "poorly water-soluble material (1a)," a crystalline poorly water-soluble material will be referred to as "crystalline (1b)" or "poorly water-soluble material (1b)," and when both are referred to collectively without distinction, they will be referred to as "poorly water-soluble material (1)."
[0015] The poorly water-soluble material (1) of the present disclosure is a poorly water-soluble substance that does not dissolve in water or dissolves only in small amounts. The poorly water-soluble material before the amorphization process contains a large amount of poorly water-soluble material (1b) in a crystalline state. The poorly water-soluble material (1b) in a crystalline state can have at least one of the following characteristics: (i) The solubility in pure water at 25° C. is 0.1% by mass or less. The solubility can be evaluated and judged in accordance with the provisions of the Japanese Pharmacopoeia as follows. Add it to pure water at 25°C at a concentration of 0.1% by mass, shake vigorously for 30 seconds every 5 minutes, and evaluate how much it dissolves within 30 minutes. If insoluble matter is found when visually observing the aqueous solution after 30 minutes, it can be determined that the solubility in pure water at 25°C is 0.1% by mass or less. (ii) The octanol / water partition coefficient (logP) is greater than 1 and not greater than 21. Preferably, it is in the range of more than 1 and not more than 9. For compounds whose molecular structures have been elucidated, the logP value can be determined in silico using calculation software such as ALOGPS (URL: http: / / www.vcclab.org / lab / alogps / ). On the other hand, for compounds whose molecular structure is unknown, it can be experimentally determined using the following formula by high performance liquid chromatography in accordance with JIS Z 7260-117 (2006). logP = log(Coc / Cwa) Coc: test substance concentration in 1-octanol layer Cwa: test substance concentration in the aqueous layer (iii) The solubility in the second fluid of the Japanese Pharmacopoeia, 16th Edition, as measured by a method in accordance with the Japanese Pharmacopoeia dissolution test (paddle method) is 3 mg / 100 mL or less.
[0016] The poorly water-soluble material (1) may be, for example, a poorly water-soluble physiologically active substance. In this specification, the physiologically active substance means a compound that acts on a living body, preferably the human body, to cause some biological reaction or to control a biological reaction.
[0017] Suitable examples of the poorly water-soluble material (1) include one or more selected from the group consisting of polyphenols, polyphenol derivatives, carotenoids, coenzyme Q10, vitamins, and sesamin. More suitable examples of the poorly water-soluble material (1) include one or more selected from the group consisting of polyphenols, polymethoxyflavonoids (PMFs) as polyphenol derivatives, and carotenoids. Even more suitable examples of the poorly water-soluble material (1) include one or more selected from polyphenols.
[0018] The poorly water-soluble material (1) may be a compound containing one or more (preferably two or more) conjugated dienes and optionally containing one or more oxygen atoms. The conjugated diene structure may be part of a ring (e.g., benzene, cyclohexadiene).
[0019] Suitable examples of such poorly water-soluble materials (1) include curcuminoids, flavonoids having a flavone skeleton, an isoflavone skeleton, a flavonol skeleton, or a flavanone skeleton, stilbenoids, phenols such as hydroxycinnamic acid and rosmarinic acid (all of which are polyphenols), carotenoids, ubiquinone (coenzyme Q10), and vitamins A, D, E, and K (all of which are vitamins). Specific examples of poorly water-soluble materials included in these groups will be described below.
[0020] 1-1. Polyphenols and polyphenol derivatives The polyphenols can be one type or a combination of two or more types. Polyphenols are plant components having two or more phenolic hydroxy groups (hydroxy groups bonded to aromatic rings such as benzene rings and naphthalene rings) in the molecule, examples of which include the following. The following examples may be compounds or compositions. 1. Curcuminoids [e.g., curcumin (including keto and enol forms), dimethoxycurcumin, bisdimethoxycurcumin], and tetrahydrocurcumin, 2. Flavonoids [L Theorin, Apigenin, Geosumi N, HSperetin, Naringenin, Hesperidin, Eriodictyol Le, Ke Lucetin, Myricetin, Silybinin, Silymarin [a mixture of flavonolignans such as silibinin, isosilibinin, silychristin, and silydianin] , Ru Chin, isoquercitrin, quercitrin , M Lysitrin , K ferols), flavanols (e.g., catechin (E), gallocatechin, epicatechin (EC), epicatechin gallate (ECg), epigallocatechin (EGC), epigallocatechin gallate (EGCg), theaflavin, theaflavin 3-gallate, theaflavin 3'-gallate, theaflavin 3,3'-gallate), isoflavones (e.g., genistein, daidzein, glycitein), anthocyanidins (e.g., cyanidin, delphinidin, malvidin, pelargonidin, peonidin, aurantidin, eurobinidin, luteolinidin, petunidin, rosinidin), procyanidins, polycyanidins], 3. Stilbenoids [e.g. resveratrol, piceatannol], 4. Tannins [e.g., condensed tannins (proanthocyanidins, oligomeric proanthocyanidins (OPCs)), hydrolyzable tannins], 5. Monophenols [e.g. hydroxytyrosol, p-tyrosol], 6. Capsaicinoids [e.g. capsaicin, dihydrocapsaicin], 7. Phenolic acids [e.g. hydroxycinnamic acids (e.g. p-coumaric acid, caffeic acid, ferulic acid), hydroxybenzoic acids (e.g. p-hydroxybenzoic acid, gallic acid, ellagic acid), rosmarinic acid], 8. The aglycone of the compound. 9. Compounds in which the hydrogen atom of at least one phenolic hydroxy group of the above compounds has been substituted with another group (e.g., acetylated products, malonylated products, methylated products, glycosides, etc.).
[0021] The polyphenol may be, for example, a synthetic product or a product isolated and purified from a natural source. Furthermore, it may be a crude product, for example, in the form of an extract derived from a natural product.
[0022] Examples of extracts derived from natural products include turmeric extract, bayberry extract, sophora japonica extract, milk thistle extract, coffee extract, licorice extract, cucumber extract, scutellaria extract, gentian (or gentian) extract, geranium extract, cholesterol and its derivatives, hawthorn extract, peony extract, ginkgo extract, scutellaria (or scutellaria) extract, carrot extract, rosa gracilis (or rosa rubra, or rosehip) extract, sappanzu (or scutellaria) extract, tormentilla extract, parsley extract, peony extract, moquat extract, quince extract, melissa extract, yarrow extract, saxifrage extract, rosemary extract, lettuce extract, tea extract (e.g., oolong tea extract, black tea extract, green tea extract), monk fruit extract, and extracts of microbial fermentation metabolites.
[0023] A polyphenol derivative refers to a compound in which the hydrogen atom of at least one phenolic hydroxyl group of the above-mentioned polyphenol is replaced with another group (e.g., an acyl group, a malonyl group, an alkyl group, a glycosyl group, etc.), resulting in zero or one phenolic hydroxyl group. Examples of polyphenol derivatives include, but are not limited to, polymethoxyflavonoids (hereinafter referred to as PMF). PMFs are compounds that have a methoxy group (-OCH 3 PMF refers to flavonoids having 4 or more methoxy groups. Preferred examples include flavones having 4 or more methoxy groups. PMF can be one type or a combination of two or more types. Examples of PMFs include the following: 4 -OCH 3 PMF with group: 5,6,7,4'-tetramethoxyflavone 5 -OCH 3 PMF with groups: tangeretin, sinensetin 6 -OCH 3 PMF with groups: Nobiletin, 3,5,6,7,3',4'-hexamethoxyflavone 7 -OCH 3 PMF with group: 3,5,6,7,8,3',4'-heptamethoxyflavone
[0024] PMF may be, for example, a synthetic product or a product isolated and purified from nature. Furthermore, it may be a crude product, for example, in the form of an extract derived from a natural product.
[0025] Preferred examples of polyphenols include curcuminoids, flavonoids, stilbenoids, and their aglycones. Of these, preferred examples of curcuminoids include curcumin. Preferred examples of flavonoids include flavones (e.g., luteolin), flavanones (e.g., hesperetin, naringenin), and flavonols (e.g., silibinin, silymarin, rutin, quercetin, myricitrin, quercitrin, and isoquercitrin). Preferred examples of stilbenoids include resveratrol. Further, suitable examples of the polyphenol derivatives include nobiletin, which is a methylated product of flavone, and tangeretin.
[0026] 1-2. Carotenoids The carotenoids can be one type or a combination of two or more types. Examples of carotenoids include the following: The following examples may be compounds or compositions. Xanthophylls [e.g., lutein, zeaxanthin, canthaxanthin, fucoxanthin, astaxanthin, antheraxanthin, violaxanthin, cryptoxanthin], carotenes [e.g., α-carotene, β-carotene, γ-carotene, δ-carotene, lycopene], and apocarotenoids [e.g., apocarotenal, bixin, crocetin]. Preferred examples thereof include xanthophylls and carotenes. Preferred examples of xanthophylls include lutein and astaxanthin. Preferred examples of carotenes include β-carotene and lycopene.
[0027] The carotenoid may be, for example, a synthetic product or a product isolated and purified from natural sources. Furthermore, it may be a crude product, for example, in the form of an extract derived from a natural product.
[0028] 1-3. Coenzyme Q10 Coenzyme Q10 can be one type or a combination of two or more types. Examples of coenzyme Q10 include ubiquinone (oxidized CoQ), ubiquinol (reduced CoQ: CoQH 2 ), and semiquinone radical intermediate (CoQH·). In the present disclosure, preferred examples of coenzyme Q10 include ubiquinol. Ubiquinol is a fat-soluble component also known as reduced coenzyme Q10, reduced coenzyme Q, reduced CoQ, or reduced UQ, and is known as an effective fat-soluble antioxidant.
[0029] Coenzyme Q10 may be, for example, a synthetic product or a product isolated and purified from natural sources. Furthermore, it may be a crude product, for example, in the form of an extract derived from a natural product.
[0030] 1-4. Vitamins The vitamins can be one or a combination of two or more. Examples of vitamins include the following, which may be compounds or compositions: Vitamin A [e.g., retinol], Vitamin D [e.g., ergosterol, ergocalciferol, cholecalciferol], Vitamin E [e.g., tocopherol, tocotrienol], Vitamin K [e.g., phylloquinone].
[0031] The vitamin may be, for example, a synthetic product or a product isolated and purified from a natural source, or may be a crude product, such as an extract derived from a natural product.
[0032] 1-5. Sesamin Sesamin is a type of lignan found in, for example, sesame, pepper, and ginkgo.
[0033] Sesamin may be, for example, a synthetic product or a product isolated and purified from natural sources. Furthermore, it may be a crude product, for example, in the form of an extract derived from a natural product.
[0034] The solid composition, which is one embodiment of the present disclosure, is a composition containing at least one selected from the group consisting of the above-mentioned poorly water-soluble materials (1) in an amorphous state, i.e., as an amorphous poorly water-soluble material (1a), together with HPMC (2) and a polysaccharide other than HPMC (3).
[0035] The content of the poorly water-soluble material (1a) in the present solid composition is not limited, but can usually be selected from a range of 1 mass% or more. It can be preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 15 mass% or more. The upper limit of the content of the poorly water-soluble material (1a) is not limited, but can usually be selected from a range of 60 mass% or less. It can be preferably 50 mass% or less, more preferably 40 mass% or less, and even more preferably 35 mass% or less. For example, it can usually be in the range of 1 to 60 mass%, preferably in the range of 5 to 50 mass%, more preferably in the range of 10 to 40 mass%, and even more preferably in the range of 15 to 35 mass%.
[0036] 2. Materials for amorphizing crystalline poorly water-soluble materials (1b) The present invention is characterized in that two or more polysaccharides are used in combination to amorphize a crystalline poorly water-soluble material (1b) to obtain an amorphous poorly water-soluble material (1a). By using two or more polysaccharides in combination, the crystalline poorly water-soluble material (1b) can be amorphized with a high yield. In addition, preferably, the amorphous state of the obtained poorly water-soluble material (1a) can be stabilized. More preferably, a solid composition containing an amorphous poorly water-soluble material (1a) can be provided that is inhibited from causing changes in appearance (e.g., caking, solidification, color change, etc.) under the influence of high temperature and humidity or during storage, and has excellent storage stability.
[0037] In one embodiment of the present disclosure, a material for amorphizing the poorly water-soluble material (1b) to prepare the amorphous poorly water-soluble material (1a) can be a combination of hydroxypropyl methylcellulose (HPMC) (2) and one or more polysaccharides other than HPMC (3). The substance used to make the poorly water-soluble material (1b) amorphous will be specifically described below.
[0038] 2-1. Hydroxypropyl methylcellulose (HPMC) (2) Hereinafter, in this specification, the second component contained in the solid composition of the present invention may be referred to as "HPMC". HPMC is a cellulose ether in which a hydroxypropoxyl group has been introduced into methylcellulose, and is a water-soluble cellulose derivative.
[0039] The HPMC used in the present disclosure is not particularly limited, but includes HPMC having the degrees of substitution with methoxy groups and hydroxypropoxy groups (content of methoxy groups and hydroxypropoxy groups) each falling within the following ranges: Degree of substitution with methoxy group: in the range of 20 to 40%, preferably 25 to 35%, more preferably 27 to 30%; Degree of substitution with hydroxypropoxy groups: in the range of 3 to 20%, preferably 5 to 15%, and more preferably 7 to 12%.
[0040] Preferably, the HPMC has a degree of substitution with a methoxy group of 25 to 35% and a degree of substitution with a hydroxypropoxy group of 5 to 15%, and more preferably, the HPMC has a degree of substitution with a methoxy group of 27 to 30% and a degree of substitution with a hydroxypropoxy group of 7 to 12%. Two or more types of HPMC can be used in combination as desired.
[0041] The HPMC used in the present disclosure is not particularly limited, but has a viscosity of 2 to 120 mm when prepared as an aqueous solution (20°C) with a concentration of 2% by mass. 2 HPMC having a viscosity in the range of 3 to 100 mm / s is preferably used. 2 / s, more preferably 4 to 80 mm 2 / s range.
[0042] Such HPMC is commercially available for use as a food additive or pharmaceutical preparation. Examples of such HPMC include Metolose (registered trademark; hereinafter the same) SE-03, Metolose SE-06, Metolose NE-100, Metolose SFE-400, Metolose NE-4000, and Metolose SFE-4000 (all manufactured by Shin-Etsu Chemical Co., Ltd.).
[0043] The content of HPMC in the present solid composition is not limited, but can usually be selected from the range of 20% by mass or more. It can be preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more. The upper limit of the content of HPMC is not limited, but can usually be selected from the range of 95% by mass or less. It can be preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less. For example, it can usually be in the range of 20 to 95% by mass, preferably in the range of 30 to 90% by mass, more preferably in the range of 35 to 85% by mass, and even more preferably in the range of 40 to 80% by mass.
[0044] 2-2. Polysaccharides with 5 or more sugars other than HPMC (3) In the present invention, the polysaccharide used in combination with HPMC is a polysaccharide other than HPMC, characterized in that it contains 5 or more constituent sugars. Hereinafter, in the present specification, the polysaccharide may be referred to as "polysaccharide (3) having 5 or more sugars" or simply as "polysaccharide (3)". The polysaccharide (3) does not include HPMC. The number of monosaccharides constituting the polysaccharide is not limited, with the limit being that the polysaccharide (3) is a polysaccharide having 5 or more sugars. It is preferable that the number of monosaccharides constituting the polysaccharide is larger than 5 sugars (e.g., molecular weight is about 800), and examples thereof include 6 sugars or more (e.g., molecular weight of α-CD is 972), 7 sugars or more (e.g., molecular weight of β-CD is 1135), 8 sugars or more (e.g., molecular weight of γ-CD is 1297), 9 sugars or more, and 10 sugars or more. The monosaccharides constituting the polysaccharides are not particularly limited, and include pentoses (including aldopentoses, ketopentoses, and their deoxy sugars) and hexoses (including aldohexoses, ketohexoses, and their deoxy sugars). Examples of these polysaccharides (3) include linear, branched, and cyclic polysaccharides. For example, cyclodextrin, which will be described later, is a cyclic water-soluble polysaccharide having a structure in which 6 to 8 monosaccharides are bonded in a ring shape.
[0045] Examples of polysaccharides (3) that may be used in combination with HPMC include, but are not limited to, gum arabic, hydroxypropyl cellulose (HPC), gum ghatti, low molecular weight gum ghatti, modified starch, locust bean gum, guar gum, alginic acid or a salt thereof, carrageenan (including ι-carrageenan, λ-carrageenan, and κ-carrageenan), pectin (including HM pectin and LH pectin), xanthan gum, pullulan, microcrystalline cellulose, fermented cellulose, methylcellulose, carboxymethylcellulose (CMC), dextrin (including resistant dextrin), cyclodextrin (including α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin), soybean polysaccharides, agar, tamarind seed gum, hydrolyzed guar gum, karaya gum, tara gum, welan gum, and gellan gum (including native gellan gum and acetylated gellan gum). Here, gum ghatti includes those having a molecular weight of 800,000 or more, and low molecular weight gum ghatti includes those having a molecular weight of less than 800,000, preferably about 100,000 to 200,000 in terms of emulsifying power. Suitable examples of polysaccharides (3) include, but are not limited to, gum arabic, HPC, low molecular weight gum ghatti, processed starch, pectin, soybean polysaccharides, pullulan, microcrystalline cellulose, fermented cellulose, tamarind seed gum, guar gum hydrolyzate, dextrin (including resistant dextrin), CMC, cyclodextrin, and carrageenan. More preferred polysaccharides (3) are gum arabic and HPC.
[0046] These polysaccharides (3) can be used alone with HPMC (2), or two or more can be used in any combination with HPMC (2). The combination is not particularly limited, but for example, HPC is a water-soluble polysaccharide that can be easily combined with any other polysaccharide (3). An example of a combination is not limited, but a preferred combination is HPC and gum arabic.
[0047] HPC is obtained by etherifying the hydroxyl groups of cellulose with propylene oxide, and contains many hydroxypropyl groups (-OCH 2 CH(OH)CH3 ) is a water-soluble cellulose derivative. The degree of substitution (DS), which is the average number of substituted hydroxyl groups per glucose, is a maximum of 3. The degree of molar substitution (MS), which is the number of hydroxypropyl groups per glucose, is 4 or more. The molecular weight of HPC, which is commercially available as a food additive, can be in the range of mass average molecular weight 40000 to 910000, but the molecular weight range can be appropriately selected and set as necessary. For example, without limitation, Celny (registered trademark, hereinafter the same) SSL (molecular weight 40000), Celny SL (molecular weight 100000), Celny L (molecular weight 140000), Celny M (molecular weight 620000), Celny H (molecular weight 910000) (all manufactured by Nippon Soda Co., Ltd.) can be mentioned. In the present disclosure, it is sufficient to have water solubility, and although not limited, preferably, a mass average molecular weight of 40000 to 140000 can be exemplified. The molecular weight of HPC can be measured by gel permeation chromatography (GPC).
[0048] The role of the polysaccharide (3) used in combination with HPMC in amorphizing the poorly water-soluble material (1b) can be considered as follows. However, this is merely a hypothesis and should not be construed as being bound by it.
[0049] When the polysaccharide (3) is added to the poorly water-soluble material (1b) together with HPMC (2), and all the components are heated and kneaded (preferably heated and kneaded at a temperature equal to or higher than the glass transition point of the poorly water-soluble material (1b)), and then cooled, the poorly water-soluble material (1a) that has been made amorphous by heating and kneading is trapped in the polysaccharides (HPMC (2) and polysaccharide (3)) until it is cooled, and as a result, recrystallization due to aggregation of the poorly water-soluble materials is prevented. For this reason, the molecular weight of the polysaccharide (3) is preferably larger than the molecular weight of the poorly water-soluble material (1b) to be amorphized. In other words, the polysaccharide (3) used to amorphize the poorly water-soluble material (1b) can be selected from among polysaccharides having a molecular weight larger than that of the poorly water-soluble material (1b) using the molecular weight of the poorly water-soluble material (1b) as an indicator. For example, the molecular weight of the polysaccharide (3) is, but is not limited to, 800 or more, 1×10 4 That's it, 5 x 10 4 or more, or 1×10 5 The above can be given as examples.
[0050] In the present invention, in order to make the poorly water-soluble material (1b) amorphous, it is not excluded to use a material other than the polysaccharide (3) in combination with HPMC. However, for example, disaccharides such as Palatinose (registered trademark; the same applies below) and maltose, trisaccharides such as raffinose, and surfactants such as polysorbate 80 in combination with HPMC may not be preferable in order to stably maintain the amorphous state of the poorly water-soluble material (1a). Therefore, in one embodiment of the present disclosure, it is preferable not to use disaccharides such as palatinose and maltose, trisaccharides such as raffinose, and surfactants such as polysorbate 80 as materials to be used in combination with HPMC to amorphize the poorly water-soluble material (1b).
[0051] The content (total amount) of polysaccharide (3) in the present solid composition can usually be selected from the range of 1% by mass or more. It can be preferably 4% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more or 12% by mass or more. The upper limit of the content of polysaccharide (3) is not limited, but can usually be selected from 80% by mass or less. It can be preferably 75% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less or 50% by mass or less. For example, it can usually be in the range of 1 to 80% by mass, preferably in the range of 4 to 75% by mass, more preferably in the range of 5 to 70% by mass, even more preferably in the range of 10 to 60% by mass.
[0052] When HPC is used alone or in combination with another polysaccharide (3) as the polysaccharide (3), the content of HPC in the present solid composition is not limited, but can be selected from a range of usually 1% by mass or more. It can be preferably 2% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more. The upper limit of the content of HPC in the present solid composition can be selected and set from a range of usually 50% by mass or less. It can be preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less. The content of HPC in the present solid composition can be usually within the range of 1 to 50% by mass, preferably within the range of 3 to 40% by mass, more preferably within the range of 5 to 30% by mass, and even more preferably within the range of 8 to 20% by mass.
[0053] The mass ratio of the amorphous poorly water-soluble material (1a) and HPMC (2) in the present solid composition, which is one embodiment of the present disclosure, can be set so that the ratio of HPMC (2) to 1 part by mass of the poorly water-soluble material (1a) is usually within the range of 0.3 to 95 parts by mass. It is preferably within the range of 0.5 to 20 parts by mass. By using the poorly water-soluble material (1b) and HPMC (2) together with the polysaccharide (3) in at least this range, the poorly water-soluble material (1b) can be amorphized stably with good yield, and the present solid composition containing the poorly water-soluble material (1a) can be obtained stably. It is more preferably within the range of 1 to 20 parts by mass, and even more preferably within the range of 3 to 20 parts by mass. By using the poorly water-soluble material (1b) and HPMC (2) together with the polysaccharide (3) in at least this range, the poorly water-soluble material (1b) can be amorphized stably with good yield, and the obtained solid composition has good storage stability and can significantly suppress changes in appearance (caking, discoloration, etc.) due to storage. In another embodiment, the ratio of HPMC (2) per part by mass of the poorly water-soluble material (1a) contained in the solid composition can be within a range of 0.6 to 18 parts by mass, more preferably within a range of 1 to 8.5 parts by mass, and even more preferably within a range of 1.5 to 5 parts by mass.
[0054] The mass ratio of the poorly water-soluble material (1b) and the polysaccharide (3) used in combination with HPMC (2) in the present solid composition, which is one embodiment of the present disclosure, can be set so that the ratio of the polysaccharide (3) to 1 part by mass of the poorly water-soluble material (1a) is usually within the range of 0.02 to 50 parts by mass. It is preferably within the range of 0.05 to 20 parts by mass. By using the poorly water-soluble material (1b) and the polysaccharide (3) in combination with HPMC (2) so as to be at least within this range, the poorly water-soluble material (1b) can be amorphized stably with good yield, and the present solid composition containing the poorly water-soluble material (1a) can be stably obtained. It is more preferably within the range of 1 to 10 parts by mass, and even more preferably within the range of 1 to 5 parts by mass. By using the poorly water-soluble material (1b) and the polysaccharide (3) together with HPMC (2) in such a manner that the poorly water-soluble material (1b) is at least in this range, the poorly water-soluble material (1b) can be stably amorphized with good yield, and the obtained solid composition has good storage stability and can significantly suppress changes in appearance due to storage (caking, discoloration, etc.). In another embodiment, the ratio of the polysaccharide (3) to 1 part by mass of the poorly water-soluble material (1a) contained in the solid composition can be preferably within the range of 0.06 to 8 parts by mass, more preferably within the range of 0.1 to 3 parts by mass, and even more preferably within the range of 0.2 to 2 parts by mass.
[0055] The mass ratio of HPMC (2) and polysaccharide (3) in the present solid composition, which is one embodiment of the present disclosure, can be set so that the ratio of polysaccharide (3) to 1 part by mass of HPMC (2) is usually within the range of 0.01 to 5 parts by mass. It is preferably within the range of 0.05 to 5 parts by mass. By using HPMC (2) and polysaccharide (3) in combination with the poorly water-soluble material (1b) so as to be at least within this range, the poorly water-soluble material (1b) can be amorphized stably with good yield, and the present solid composition containing the poorly water-soluble material (1a) can be obtained stably. It is more preferably within the range of 0.05 to 1 part by mass, and even more preferably within the range of 0.05 to 0.5 parts by mass. By using HPMC (2) and polysaccharide (3) in combination with the poorly water-soluble material (1b) so as to be at least within this range, the poorly water-soluble material (1b) can be amorphized stably with good yield, and the obtained solid composition has good storage stability and can significantly suppress changes in appearance (caking, discoloration, etc.) due to storage. In another embodiment, the ratio of the polysaccharide (3) to 1 part by mass of the HPMC (2) can be within the range of 0.01 to 2.5 parts by mass, preferably within the range of 0.03 to 1.3 parts by mass, more preferably within the range of 0.06 to 0.9 parts by mass, and even more preferably within the range of 0.1 to 0.5 parts by mass.
[0056] The present solid composition is characterized by having a solid form. Such solid forms include powder, granule, block, and rod forms. As described below, the present solid composition is used to prepare a product having a desired form (e.g., formulation form) by mixing with any other additive that does not affect the crystal state (ratio of crystalline and amorphous) of the poorly water-soluble material (1). In this case, the present solid composition is preferably prepared in a powder or granular form.
[0057] In this case, the particle size of the powder or granules can be appropriately selected depending on the form. For example, the particle size (median size; the same applies below) can be within the range of 0.1 to 2000 μm, 1.0 to 1000 μm, 10 to 500 μm, 100 to 500 μm, 100 to 400 μm, 1 to 100 μm, 5 to 100 μm, or 10 to 100 μm. In the solid composition of the present invention, the smaller the particle size, the larger the surface area, and the faster the speed of reaching supersaturation.On the other hand, if there is a large amount of coarse powder, it will cause problems such as not being able to fill hard capsules or being unable to make tablets, so the particle size may be adjusted by means such as pulverization using a pulverizer.In addition, the particle size (median size) can be measured according to the description of the examples described below.
[0058] The amorphous state of the poorly water-soluble material (1) contained in the solid composition of the present invention can be confirmed by powder X-ray diffraction. Powder X-ray diffraction is a method commonly used to detect crystalline substances contained in a sample. In a chart obtained by this method, scattered light due to amorphous substances is detected as a broad peak (in the present invention, this is referred to as a "halo peak"), and diffracted light due to crystalline substances is detected as a sharp peak (in the present invention, this is referred to as a "sharp peak"). The amorphous state of the poorly water-soluble material (1) contained in the solid composition of the present invention can be simply evaluated based on a value (also referred to as the "XRD analysis value" in the present invention) obtained by analyzing the solid composition with a powder X-ray diffractometer (XRD analysis chart), where the area of the halo peak in the range of 2θ=5 to 60° is (S1) and the area of the sharp peak (the part beyond the halo peak) derived from the poorly water-soluble material (1b) in a crystalline state in the same range is (S2). The smaller this value (XRD analysis value) is, the more the poorly water-soluble material in the amorphous state (1a) is contained in the poorly water-soluble material contained in the solid composition. However, it cannot be quantified with high accuracy, and does not indicate the specific proportion of the poorly water-soluble material in the amorphous state (1a) contained in the sample.
[0059] In the solid composition, the XRD analysis value is, for example, 4.0% or less, 3.0% or less, 2.0% or less, 1.0% or less, 0.8% or less, 0.5% or less, or 0%. The solid composition preferably has an XRD analysis value of 1.0% or less. More preferably, the solid composition has an XRD analysis value of 0%, and such solid composition is substantially or completely free of the crystalline poorly water-soluble material (1b).
[0060] Since the crystallinity of the water-insoluble material (1) contained in the solid composition has been reduced or disappeared, it is considered that the solid composition has excellent disintegration, dispersibility, elution property and / or non-aggregation property when it comes into contact with an aqueous medium (e.g., water, body fluid). Therefore, when this solid composition is administered to a living body, it is expected that the maximum blood concentration (Cmax) of the poorly water-soluble material (1a) contained in the composition will be increased, and that the total amount of the material absorbed into the blood will be increased.
[0061] Due to this property, the solid composition can allow the poorly water-soluble material (1) to exhibit its functions (e.g., biological activity) to a high degree.
[0062] Furthermore, the present solid composition is inhibited from caking and changing in color due to storage, and has excellent storage stability.
[0063] The present solid composition can be produced, for example, by the production method described below (sometimes referred to in this specification as the "production method of the present invention"). <Method for producing a solid composition containing an amorphous poorly water-soluble material (1a)> The solid composition may, for example, Crystalline, poorly water-soluble material (1b), HPMC(2), and Polysaccharides with 5 or more sugars other than HPMC (3) The method can be produced by a production method including a step of heating and kneading the above-mentioned components. The heating and kneading step can change the crystalline poorly water-soluble material (1b) into an amorphous state.
[0064] The heating and kneading step is not particularly limited as long as it can melt the crystalline poorly water-soluble material (1b), and can be carried out according to a standard method in the art. For example, a method for making the crystalline poorly water-soluble material (1b) amorphous is a method of heating the crystalline poorly water-soluble material (1b) until it melts. On the other hand, the organic solvent method of dissolving the crystalline poorly water-soluble material (1b) in an organic solvent (which may involve heating or stirring to increase solubility) is not included in the method of the present invention, since the composition of the present solid composition does not allow the preparation of a high-purity amorphous preparation.
[0065] In the production method of the present invention, since no organic solvent is used, it is necessary to heat the crystalline poorly water-soluble material (1b) to a temperature at which it melts. In addition, when a material having high viscoelasticity (e.g., xanthan gum, etc.) is used among the HPMC (2) and polysaccharide (3) used in combination to maintain the amorphous state, a certain degree of torque is required in the kneading step. In this regard, the heat kneading step that can be used in the production method of the present invention can be suitably carried out by using, for example, a kneader or mixer, which is capable of controlling temperature; or an extruder, such as a single-screw extruder, an intermeshing screw extruder, or a multi-screw extruder (e.g., a twin-screw extruder). With a kneader, it is possible to create a state in which the materials are uniformly mixed by performing multiple operations (kneading operations) such as mixing, crushing, kneading, and pounding in parallel, and to change the crystalline poorly water-soluble material (1b) to an amorphous state. The extruder is a machine that can perform the kneading operation and extrusion simultaneously or continuously. The extruder, like the kneader, can mix the materials uniformly and convert the crystalline poorly water-soluble material (1b) into an amorphous form, and then the resulting solid composition containing the amorphous poorly water-soluble material (1a) can be discharged by extrusion.
[0066] In the heat-kneading step that can be used in the production method of the present invention, for example, the poorly water-soluble material (1b) is preferably kneaded with HPMC (2) and polysaccharide (3) at a temperature equal to or higher than the glass transition temperature Tg (°C) of the poorly water-soluble material (1b). When two or more poorly water-soluble materials (1b) are used in combination, the heat-kneading can be performed at a temperature equal to or higher than the glass transition temperature Tg (°C) of the poorly water-soluble material (1b) having the highest glass transition temperature. The glass transition temperature (Tg) can be determined in accordance with JIS K 7121:2012. For example, when the poorly water-soluble material (1b) is a curcuminoid, its glass transition temperature Tg is 72°C, so that the heat-kneading temperature can be 80°C or higher, preferably higher than 80°C. Therefore, for example, the kneading temperature when amorphizing the curcuminoid can be 100°C or more, 110°C or more, 120°C or more, 130°C or more, 140°C or more, 150°C or more, or 160°C or more.
[0067] The upper limit of the temperature employed in the heat kneading is not particularly limited, but may be, for example, from the melting point Tm+40 (°C) to Tm-10 (°C) of the poorly water-soluble material (1b). When two or more poorly water-soluble materials (1b) are used in combination, the melting point Tm (°C) refers to the melting point Tm (°C) of the material with the highest melting point. The melting point (Tm) can be determined in accordance with JIS K 7121-1987. The upper limit of the temperature is desirably a temperature at which the polysaccharide (3) is not excessively decomposed, for example, 240° C. or lower, preferably 230° C. or lower, and more preferably 220° C. or lower.
[0068] For example, when the poorly water-soluble material (1b) is a curcuminoid, its melting point is 191°C, so the kneading temperature can be 231°C or less, 220°C or less, 210°C or less, 200°C or less, 190°C or less, or 180°C or less. That is, when the poorly water-soluble material (1b) is a curcuminoid, the temperature employed for the heat kneading can be within the range of 100°C to 231°C, 120°C to 220°C, or 120°C to 200°C, for example.
[0069] The kneading step may be a step of heating and kneading the above-mentioned poorly water-soluble material (1b) together with other components (4) in addition to the HPMC (2) and the polysaccharide (3).
[0070] In one embodiment, the manufacturing method of the present disclosure may include a step of preparing the present solid composition containing the amorphous poorly water-soluble material (1a) by heating and kneading the poorly water-soluble material (1b), HPMC (2), and polysaccharide (3) in the kneading step, and then cooling the present solid composition to a desired temperature such as room temperature. Furthermore, the method may include a step of disintegrating or pulverizing the solid composition thus obtained with a disintegrator, a grinder, or the like. In addition to the kneading step, or the cooling step, or the crushing / pulverizing step, the production method of the present disclosure can also be produced by a method having a solid-liquid separation step (e.g., solvent precipitation), a drying step (e.g., spray drying, freeze drying, vacuum drying, etc.), a granulation step (sieving, etc.), and / or a granulation step. These methods can be carried out according to standard methods in the art.
[0071] <Uses of the solid composition> The above-mentioned solid composition can be used as it is as a raw material for oral compositions, medicines, quasi-drugs, food and beverages, oral care products, or cosmetics. In addition, since the solid composition contains a very high proportion of the poorly water-soluble material (1a) in an amorphous state, the same poorly water-soluble material (1b) raw material before amorphization may be added to it for use. In this way, the advantage of adding the raw material powder before amorphization is that when the absorbability of the amorphous preparation in the body is too high, the amount of absorption can be easily adjusted, and the physical properties such as the hygroscopicity of the powder can be easily adjusted. In this case, the poorly water-soluble material (1) contained in the preparation may be adjusted, for example, in the range of amorphous:crystalline = 1:0.1 to 1:5 (mass ratio), preferably amorphous:crystalline = 1:2.
[0072] Furthermore, the solid composition can be mixed with other ingredients (e.g., ingredients of medicines, quasi-drugs, foods and beverages, oral care products, or cosmetics, or additives therefor) as necessary so as not to affect the amorphous state of the poorly water-soluble material (1a) contained therein, and can be used to prepare desired medicines, quasi-drugs, foods and beverages, oral care products, or cosmetics.
[0073] Examples of other additives include, but are not limited to, binders, disintegrants, lubricants, excipients, colorants, flavorings, fragrances, flavor oils, surfactants, preservatives, antioxidants, UV absorbers, moisturizers, and pH adjusters. These ingredients include those that are specified as additives in the fields of pharmaceuticals, quasi-drugs, and foods.
[0074] More specifically, examples of such surfactants include sucrose, fructose, starches, cellulose, dextrin, powdered gum arabic, powdered guddi gum, methylcellulose, crystalline cellulose, ethylcellulose, polyvinylpyrrolidone, polyethylene glycol, talc, silicon dioxide, magnesium stearate, stearic acid, stearyl alcohol, hydroxypropyl starch, sodium carboxymethyl starch, powdered agar, carboxymethylcellulose (calcium), ester oil, wax, higher fatty acids, higher alcohols, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, and polyhydric alcohols.
[0075] The aforementioned foods and beverages include, in addition to general foods and beverages, for example, health foods, functional foods, dietary supplements (or supplements), nutritional functional foods, dietary supplements, special purpose foods, and foods for specified health uses, without limitation. Oral care products include, for example, toothpastes (powders, pastes), oral odor prevention and deodorants (gum, tablets, etc.), periodontal disease prevention and improvement agents, without limitation. Cosmetics include, for example, functional cosmetics, skin care products, makeup products, cosmetics, and hair care products. The present solid composition itself, or a final product containing the same, can be a composition to be orally administered or orally ingested (e.g., oral medicines, foods and beverages), a composition to be applied to the oral cavity (e.g., oral care products), a composition to be applied to the bronchi and lungs, a composition to be administered to the eyes, a composition to be administered to the ears, a composition to be applied to the nose, a composition to be applied to the rectum, a composition to be applied to the vagina, or a composition to be applied to the skin.
[0076] Examples of product forms containing the present solid composition include tablets (e.g., uncoated tablets, sugar-coated tablets, multi-layer tablets, orally disintegrating tablets, chewable tablets, effervescent tablets, dispersible tablets, dissolving tablets, etc.), capsules, granules (e.g., effervescent granules), powders, oral jellies, oral tablets (e.g., troches, sublingual tablets, buccal tablets, adhesive tablets, gums, etc.), oral sprays, oral semisolids, mouthwashes, dialysis agents (e.g., peritoneal dialysis agents, hemodialysis agents), inhalants (e.g., inhalation powders, inhalation aerosols), suppositories, rectal semisolids, enemas, eye ointments, ear drops, nasal drops (nasal powders), vaginal tablets, vaginal suppositories, external solids (e.g., external powders), and sprays (e.g., external aerosols, pump sprays). The present solid composition can also be mixed with a liquid when used to prepare a liquid formulation. Such dosage forms include oral liquids (e.g., elixirs, suspensions, emulsions, and lemonades), syrups (e.g., syrup preparations), oral sprays, inhalation solutions, enemas, nasal solutions, external solutions (e.g., liniments and lotions), and sprays (e.g., external aerosols and pump sprays).
[0077] <How to calculate the percentage of crystalline and / or amorphous matter in poorly water-soluble materials> The calculation method according to one embodiment of the present disclosure (hereinafter referred to as "the calculation method") can be useful for calculating the proportion of crystalline and / or amorphous water-soluble material contained in the water-soluble material (1) in a solid composition containing the water-soluble material (1), HPMC (2), and a polysaccharide other than HPMC having five or more sugars (3).
[0078] The solid composition includes the above-mentioned solid composition of the present invention and the solid composition obtained by the above-mentioned production method of the present invention, as well as a solid composition containing a poorly water-soluble material (1), HPMC (2), and polysaccharide (3) like the above-mentioned solid composition but produced by a non-crystallization method different from the production method of the present invention. Also included is a solid composition prepared by adding (externally adding) a crystalline poorly water-soluble material (1b) to the solid composition obtained by the production method of the present invention. The solid composition may be a medicine, a quasi-drug, a food or drink, an oral care product, or a cosmetic, or may be a material to be added to each of these products. Hereinafter, the solid composition to be measured in this calculation method is referred to as the "measurement solid composition" or "measurement sample." The poorly water-soluble material (1), HPMC (2), and polysaccharide (3) constituting the measurement solid composition (measurement sample) are as described above, and the above descriptions are incorporated herein by reference.
[0079] This calculation method can be carried out by the following steps (A) and (B): (A) determining an XRD analysis value in a chart obtained by analyzing a solid composition to be measured (a measurement sample) with a powder X-ray diffractometer; and (B) A process for calculating the proportion of crystalline (1a) and / or amorphous (1b) in the water-insoluble material contained in the solid composition to be measured (measurement sample) by applying the XRD analysis value of (A) to a calibration curve prepared in advance.
[0080] The calibration curve can be prepared by the following method: (C) For the poorly water-soluble material (1) contained in the measurement solid composition (measurement sample), the XRD analysis value of each standard sample is obtained for a mixture (standard sample) in which a crystalline poorly water-soluble material (1b) is mixed in various ratios with a composition in which the crystalline poorly water-soluble material (1b) is made amorphous using the manufacturing method of the present invention, and the ratio (%; theoretical value) of the crystalline poorly water-soluble material (1b) in the standard sample is plotted on the X-axis, and the XRD analysis value is plotted on the Y-axis. Instead of the ratio of the crystalline poorly water-soluble material (1b) in the standard sample, the ratio (%; theoretical value) of the crystalline (1b) in the poorly water-soluble material (total amount) contained in the standard sample can also be plotted on the X-axis. The XRD analysis value is as described above. The step of creating the calibration curve may be carried out before the steps (A) and (B).
[0081] The calculation method including the steps (A) and (B), or further including the step (C), can be used based on the fact that the production method of the present invention makes it possible to prepare a solid composition with an extremely high amorphous content, and is based on the fact that, as shown in Test Example 6 described later, for a solid composition containing a poorly water-soluble material (1), HPMC (2), and a polysaccharide (3), the XRD analysis value shows a positive correlation with the proportion of crystalline (1a) of the poorly water-soluble material contained in the solid composition, or the proportion of crystalline (1a) in the poorly water-soluble material (1). In other words, by creating a calibration curve reflecting the correlation between the two in advance and determining the XRD analysis value of a measurement sample, the proportion of crystalline (1a) of the poorly water-soluble material contained in the measurement sample, or the proportion of crystalline (1a) in the poorly water-soluble material (1), can be easily known from the calibration curve. In addition, if the proportion of crystalline (1a) in the poorly water-soluble material (1) (crystalline content %) is known, the proportion of amorphous (1b) in the poorly water-soluble material (1) can also be known at the same time.
[0082] The standard sample used in (A) may be prepared by appropriately selecting a mixing ratio within the range of the composition obtained by amorphizing a poorly water-soluble material by the production method of the present invention: the crystalline poorly water-soluble material (1b)=1:0.1 to 1:10, and preparing two or more samples with different mixing ratios.
[0083] According to this calculation method, it becomes possible to calculate the proportion of crystalline and / or amorphous matter in the water-insoluble material contained in a solid composition, and to evaluate or control the quality of the solid composition. EXAMPLES
[0084] The present invention will be described in more detail below with reference to test examples and examples. However, the present invention is not limited to these, and many modifications are possible within the technical concept of the present invention. The following tests were carried out at room temperature (25±5°C) and atmospheric pressure conditions unless otherwise specified. Furthermore, "%" means "% by mass" and "parts" means "parts by mass", respectively, unless otherwise specified.
[0085] The manufacturing methods and test methods used in the following tests are as follows. (1) Method for producing a solid composition <Heat kneading method> All the raw materials were mixed uniformly and heated and kneaded using an extruder (twin-screw extruder) (product: Process 11; manufactured by Thermo Fisher Scientific) (detailed conditions are as shown in Tables 2, 3, 5 to 8, 11, and 12). After the heating and kneading, the composition extruded and discharged in a rod state was pulverized using a pulverizer to obtain a powdered solid composition (median diameter: about 100 μm to 400 μm). The particle diameter of the pulverized material was measured using a Microtrac MT3300EX II (manufactured by Microtrac Bell) under the following measurement conditions.
[0086] <Particle size measurement conditions> Measurement mode: Dry Dry feeder: Turbotrac One-Shot Dry Set Zero time: 5 seconds Measurement time: 5 seconds Particle refractive index: 1.81 Particle shape: non-spherical
[0087] (2) Test method (2-1) Content and residual content rate (%) of poorly water-soluble materials contained in the solid composition The content of the poorly water-soluble material in the produced solid composition was measured, and the content ratio (measured value (%)) in 100% of the solid composition was calculated. The content of the poorly water-soluble material was measured by absorbance method for astaxanthin, and by HPLC method for the other poorly water-soluble materials. As shown in the formula below, the obtained measured value (%) was divided by the proportion blended during production (theoretical value (%)), and the percentage of the obtained value was taken as the "residual content rate (%) of poorly water-soluble material." Residual content rate of poorly water-soluble materials (%) = "Measured value (%) / Theoretical value (%)" x 100
[0088] (a) Measurement of curcumin content (i) Preparation of measurement samples and standard samples Curcumin 1 (Nagara Science Co., Ltd.) was dissolved in methanol, diluted with 50% acetonitrile water to 0.4 to 40 μg / ml, and filtered through a 0.45 μm membrane filter to prepare a standard sample. Moreover, the produced solid composition was diluted about 1000 to 1250 times with 50% acetonitrile water, and filtered through a 0.45 μm membrane filter to prepare a measurement sample.
[0089] The standard sample and the measurement sample were subjected to HPLC analysis under the following conditions. (ii) Measurement conditions HPLC equipment: Agilent 1220 Infinity II LC system (Agilent Technologies Japan, Ltd.) Stationary phase: Atlantis T3 column (silica-based reversed phase C 18 )(2.1×150mm, 3μm)(Waters, the same below) Mobile phase: 50% (v / v) acetonitrile aqueous solution containing 0.1% (v / v) phosphoric acid Flow rate: 0.5 ml / min Column temperature: 40℃
[0090] (b) Measurement of silymarin content (i) Preparation of measurement samples and standard samples Silybin (mixture of Silybin A and Silybin B) (Tokyo Chemical Industry Co., Ltd.) was dissolved in methanol, then diluted with 35% methanol water to 0.4-40 μg / ml (total amount of silybin), and filtered through a 0.45 μm membrane filter to prepare a standard sample. In addition, the produced solid composition was dissolved in 65% aqueous methanol, then diluted 1000-fold with 35% aqueous methanol, and filtered through a 0.45 μm membrane filter to prepare a measurement sample. The standard sample and the measurement sample were subjected to HPLC analysis under the following conditions. The silymarin content was calculated using a calibration curve of a silybin standard sample containing 98.7% silybin (as the total amount of silybin A and silybin B).
[0091] (ii) Measurement conditions HPLC equipment: Agilent 1220 Infinity II LC system Stationary phase: Atlantis T3 column (2.1 x 150 mm, 3 μm) Mobile phase: A: 0.2% (v / v) phosphoric acid aqueous solution, B: methanol Flow rate: 0.6 ml / min Column temperature: 40℃ Mobile phase gradient conditions: Table 1 [Table 1]
[0092] (c) Measurement of luteolin content (i) Preparation of measurement samples and standard samples 3',4',5,7-Tetrahydroxyflavone (Tokyo Chemical Industry Co., Ltd.) was dissolved in ethanol, then diluted with 40% acetonitrile water to 0.4 to 40 μg / ml, and filtered through a 0.45 μm membrane filter to prepare a standard sample. In addition, the produced solid composition was dissolved in 50% ethanol in water, then diluted 1000-fold with 40% acetonitrile in water, and filtered through a 0.45 μm membrane filter to prepare a measurement sample. The standard sample and the measurement sample were subjected to HPLC analysis under the following conditions.
[0093] (ii) Measurement conditions HPLC equipment: Agilent 1220 Infinity II LC system Stationary phase: Atlantis T3 column (2.1 x 150 mm, 3 μm) Mobile phase: 40% (v / v) acetonitrile aqueous solution containing 0.1% (v / v) phosphoric acid Flow rate: 0.3 ml / min Column temperature: 40℃
[0094] (d) Measurement of naringenin and hesperetin content (i) Preparation of measurement samples and standard samples Naringenin (Tokyo Chemical Industry Co., Ltd.) or Hesperetin (Tokyo Chemical Industry Co., Ltd.) was dissolved in methanol, diluted with 20% acetonitrile water to 0.4 to 40 μg / ml, and filtered through a 0.45 μm membrane filter to prepare standard samples. In addition, the prepared solid composition was dissolved in 50% acetonitrile water, then diluted 1000 times with 20% acetonitrile water, and filtered through a 0.45 μm membrane filter to prepare a measurement sample. The standard sample and the measurement sample were analyzed by HPLC under the following conditions.
[0095] (ii) Measurement conditions HPLC equipment: Agilent 1220 Infinity II LC system Stationary phase: Atlantis T3 column (2.1 x 150 mm, 3 μm) Mobile phase: A: 0.2% (v / v) phosphoric acid aqueous solution, B: acetonitrile Flow rate: 0.6 ml / min Column temperature: 40℃ Mobile phase gradient conditions: Table 2 [Table 2]
[0096] (e) Measurement of polymethoxyflavonoid (PMF) content (i) Preparation of measurement samples and standard samples Nobiletin (Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in acetonitrile, then diluted with 50% acetonitrile water to 0.4 to 40 μg / ml, and filtered through a 0.45 μm membrane filter to prepare a standard sample. In addition, the produced solid composition was dissolved in acetonitrile, then diluted 1250-fold with 50% acetonitrile water, and filtered through a 0.45 μm membrane filter to prepare a measurement sample. The standard sample and the measurement sample were subjected to HPLC analysis under the following conditions. The PMF content was calculated using a calibration curve of a nobiletin standard sample.
[0097] (ii) Measurement conditions HPLC equipment: Agilent 1220 Infinity II LC system Stationary phase: Atlantis T3 column (2.1 x 150 mm, 3 μm) Mobile phase: 50% (v / v) acetonitrile aqueous solution containing 0.1% (v / v) phosphoric acid Flow rate: 0.5 ml / min Column temperature: 40℃
[0098] (f) Measurement of sesamin content (i) Preparation of measurement samples and standard samples (+)-Sesamin and (+)-Episesamin (both from Nagara Science Co., Ltd.) were each dissolved in methanol, then diluted with 70% methanol water to approximately 0.4 to 40 μg / ml, and filtered through a 0.45 μm membrane filter to prepare standard samples. In addition, the produced solid composition was dissolved in 50% aqueous methanol, then diluted 1000-fold with 70% aqueous methanol, and filtered through a 0.45 μm membrane filter to prepare a measurement sample. The standard sample and the measurement sample were subjected to HPLC analysis under the following conditions. The (+)-Sesamin content and (+)-Episesamin content were calculated separately, and the sum of these values was regarded as the sesamin content.
[0099] (ii) Measurement conditions HPLC equipment: JASCO LC-2000Plus series system (JASCO Corporation) Stationary phase: L-column2 ODS column (4.6 x 250 mm, 5 μm) (Chemicals Evaluation and Research Institute, Japan) Mobile phase: 70% (v / v) methanol in water Flow rate: 1.0 ml / min Column temperature: 30℃
[0100] (g) Measurement of resveratrol content (i) Preparation of measurement samples and standard samples Resveratrol (Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in methanol, diluted with 25% acetonitrile water to 0.4 to 40 μg / ml, and filtered through a 0.45 μm membrane filter to prepare a standard sample. In addition, the produced solid composition was dissolved in 50% aqueous methanol, then diluted 1000-fold with 50% aqueous acetonitrile, and filtered through a 0.45 μm membrane filter to prepare a measurement sample. The standard sample and the measurement sample were subjected to HPLC analysis under the following conditions.
[0101] (ii) Measurement conditions HPLC equipment: Agilent 1220 Infinity II LC system Stationary phase: Atlantis T3 column (2.1 x 150 mm, 3 μm) Mobile phase: 25% (v / v) acetonitrile aqueous solution containing 0.15% (v / v) phosphoric acid Flow rate: 0.6 ml / min Column temperature: 40℃
[0102] (h) Measurement of astaxanthin content The total carotenoid content in the solid composition after production was measured by absorbance method. (i) Preparation of measurement samples A specific amount of the produced solid composition was weighed out (sample weighed amount), which was then diluted 2500 to 5000 times with acetone containing 1.2 mM BHT (dibutylhydroxytoluene), and filtered through a 0.2 μm membrane filter to obtain a measurement sample.
[0103] (ii) Measurement conditions The absorbance of the measurement sample was measured using a spectrophotometer JASCO V-660DS (manufactured by JASCO Corporation). Specifically, the absorbance A at the maximum absorption wavelength around 474 nm was measured using 1.2 mM BHT-containing acetone as a control solution, and the percentage (%) of the total carotenoids contained in the measurement sample was calculated using the following formula.
number
[0104] (2-2) Evaluation of amorphousness of solid compositions <Powder X-ray diffractometer (XRD) analysis> The crystallinity of the solid composition was evaluated by XRD analysis of each of the samples immediately after production (initial) and after storage for one week to one month after production (after storage). The storage was performed by placing the solid composition immediately after production in a low-density polyethylene bag (product name "Unipack A-8", manufactured by Seizo Nippon Co., Ltd.) and leaving it in a dark place at 40°C or 60°C, relative humidity 75% or normal humidity (relative humidity 45-85%) for one week to one month.
[0105] (i) Measurement conditions The solid composition immediately after production and the solid composition after storage were subjected to the following powder X-ray diffraction apparatus. Powder X-ray diffractometer: Smart Lab (Rigaku) Condition: Concentration method X-ray power: 3kW Range: 5~60° Step width: 0.05° Detector: D / teX Ultra250 Optical system: CBO-E (for concentration method) Analysis software: Smart Lab Studio II
[0106] From the obtained XRD analysis results, the area (S2) of the sharp peak (peak derived from the poorly water-soluble material (1b) in a crystalline state) in the range of 2θ=5 to 60°, and the total area ((S1)+(S2)) of the area (S2) and the area (S1) of the halo peak were calculated using software PDXLII (Rigaku Corporation) according to the manual. Based on the XRD analysis values calculated by applying these values to the following formula, the degree of amorphization was evaluated according to the following criteria.
[0107] [XRD analysis value] {(S2) / ((S1)+(S2))}×100(%) [Evaluation criteria for degree of amorphization] ◎: XRD analysis value is 1.0% or less. ◯: The XRD analysis value is greater than 1.0% and equal to or less than 4.0%. ×: XRD analysis value is greater than 4.0%.
[0108] (2-3) Appearance evaluation of solid composition The appearance of the solid composition was evaluated (color change, presence or absence of caking, presence or absence of solidification). The evaluation was performed visually for each sample immediately after production (initial stage) and after storage for 1 week to 1 month after production (post-storage). Here, "caking" refers to a state in which the powder is solidified but returns to a powder state when loosened, and "solidification" refers to a state in which the powder remains solidified and does not return to a powder state even if you try to loosen it. The storage conditions other than the period were the same as those for the crystallinity evaluation.
[0109] Test Example 1 (Examples 1 to 4, Comparative Examples 1 to 5) As shown in Table 4, each material was mixed in each ratio, and powder-shaped solid compositions (Examples 1 to 4, Example 1', and Comparative Examples 1 to 5) were produced using the above-mentioned heat kneading method and a pulverizer. The materials used and their details are shown in Table 3 below. [Table 3]
[0110] [Table 4]
[0111] These solid compositions were evaluated for the content (residual content) of the poorly water-soluble material (1), the degree of amorphization, and the appearance by the methods described above (FIGS. 1-1 and 1-2).
[0112] As shown in FIG. 1-1, in the solid compositions (Examples 1-4 and Example 1') produced using gum arabic as polysaccharide (3) or using gum arabic in combination with HPC, it was confirmed that the curcumin (poorly water-soluble material) blended as an ingredient was highly amorphous. The amorphous nature of the curcumin was stable over a long period of time. Furthermore, there was no significant change in appearance (color change, caking or solidification), and the physical properties were also stable. On the other hand, as shown in FIG. 1-2, the solid compositions (Comparative Examples 1 and 5) produced using reduced palatinose, a disaccharide, or raffinose, a trisaccharide, instead of polysaccharide (3) had good amorphous nature immediately after production, but after storage, many peaks of recrystallized curcumin were observed, and changes in appearance (caking) were observed. In addition, in the solid composition (Comparative Example 3) produced by using maltose, a disaccharide, instead of polysaccharide (3), and the solid composition (Comparative Example 2) produced by using polysorbate 80, a surfactant, a peak of the curcumin crystallization was observed immediately after preparation, and the peak became more prominent after storage, and changes in appearance (caking, browning) were observed. In addition, in the solid composition (Comparative Example 4) produced without blending HPMC (2), a peak of the curcumin crystallization was observed immediately after preparation, and the peak became more prominent after storage, and changes in appearance (solidification, browning) were observed. For this reason, Comparative Examples 1 to 5 were determined to be solid compositions that do not exhibit the effects of the present invention, even without calculating the XRD analysis values.
[0113] From the above, it was confirmed that in order to stably convert the water-insoluble material (1b) into an amorphous state while maintaining a high content, it is effective to use a polysaccharide (3) such as gum arabic or HPC in combination with HPMC (2) when heating and kneading the water-insoluble material (1b), that is, to heat and knead the water-insoluble material (1b) in the presence of polysaccharide (3) and HPMC (2).
[0114] Test Example 2 (Examples 5 to 12) The materials shown in Table 5 were mixed in the respective proportions, and each solid composition (Examples 5 to 12) was produced by the above-mentioned production method (heat kneading method).
[0115] [Table 5]
[0116] These solid compositions were evaluated for the content of the poorly water-soluble material (residual content rate), the degree of amorphization, and the appearance by the methods described above (FIGS. 2-1 and 2-2).
[0117] As shown in Fig. 2, it was confirmed that the solid compositions (Examples 5 to 12) produced using gum arabic or a combination of gum arabic and HPC as polysaccharide (3) contained highly amorphous curcumin (a poorly water-soluble material) added as an ingredient. Although caking was observed after storage in the compositions of Examples 5, 6, 11, and 12, the results of XRD analysis showed that no crystalline curcumin was observed in any of Examples 5 to 12, and the amorphous state was maintained.
[0118] From the results of Test Examples 1 and 2, it was confirmed that a solid composition having a curcumin (poorly water-soluble material (1b)) content of 4 to 60%, an HPMC (2) content of 20 to 90%, and a polysaccharide (3) content of 4 to 75% in the solid composition, and having the proportions of each component within the ranges (1) to (3) below (mass ratio), can be successfully amorphousized by the heat kneading method while containing a high proportion of curcumin. (1) Poorly water-soluble material (1b): HPMC (2) = 1:0.5~1:20 (2) Poorly water-soluble material (1b): Polysaccharide (total with HPMC) = 1:0.05 to 1:20 (3) HPMC (2): other polysaccharides (3) = 1:0.05 to 1:5.
[0119] Furthermore, it has been confirmed that by further adjusting the ratio of each component within these ranges to fall within the ranges (1') to (3') below (mass ratio), a solid composition having excellent physical stability and suppressed change in appearance after storage can be obtained. (1') Poorly water-soluble material (1b):HPMC(2)=1:3~1:20 (2') Poorly water-soluble material (1b): Polysaccharide (total with HPMC) = 1:1 to 1:5 (3') HPMC (2): other polysaccharides (3) = 1:0.05 to 1:0.5.
[0120] Test Example 3 (Examples 13 to 38) Instead of the gum arabic used in Test Examples 1 and 2, various other polysaccharides (3) were used to produce various solid compositions (Examples 13 to 38) in the same manner as Test Example 1, and the presence or absence of amorphization of curcumin (a poorly water-soluble material) and the storage stability (amorphousness and change in appearance) of the solid compositions were evaluated.
[0121] Specifically, the materials shown in Tables 7 to 10 were mixed in the respective ratios and the powder-shaped solid compositions (Examples 13 to 38) were produced using the heat-kneading method and pulverizer described above. The details of the materials used are shown in Table 6 below. [Table 6]
[0122] [Table 7]
[0123] [Table 8]
[0124] [Table 9]
[0125] [Table 10]
[0126] These solid compositions were evaluated for the content (residual content) of curcumin (poorly water-soluble material), the degree of amorphization, and the appearance by the methods described above (FIGS. 3-1 to 3-7).
[0127] As shown in Figures 3-1 to 3-7, it was confirmed that the solid compositions (Examples 13 to 38) produced by using HPMC (2) and polysaccharides (molecular weight 972 or more) (3) in combination had highly amorphous curcumin (poorly water-soluble material (1b)) blended as a material. The amorphous nature of the curcumin was stable over a long period of time. Although the solid compositions (Examples 37 and 38) produced by using λ-carrageenan showed some change in appearance (caking) due to storage, the solid compositions (Examples 13 to 36) produced by using other polysaccharides (3) showed almost no change in appearance (color change, caking or solidification) and were stable in physical properties. It was also confirmed that the crystalline peaks observed in the XRD analysis of Examples 33 and 34 were derived from dextrin and not from curcumin (data not shown).
[0128] Test Example 4 (Examples 39 to 50, Comparative Example 6) Instead of the curcumin used in Test Examples 1 to 3 as the poorly water-soluble material, other poorly water-soluble materials were used to produce various solid compositions (Examples 39 to 50, Comparative Example 6) in the same manner as Test Example 1, and the presence or absence of amorphization of the various poorly water-soluble materials and the storage stability (amorphousness and change in appearance) of the solid compositions were evaluated.
[0129] Specifically, the materials shown in Tables 12 and 13 were mixed in the respective ratios, and powdered solid compositions (Examples 39 to 50, Comparative Example 6) were produced by the above-mentioned production method (heat kneading method). Table 11 shows the details of the materials used. [Table 11]
[0130] [Table 12]
[0131] [Table 13]
[0132] These solid compositions were evaluated for the content of the poorly water-soluble material (residual content rate), the degree of amorphousness, and the appearance by the methods described above (FIGS. 4-1 to 4-4). As shown in Figures 4-1 to 4-4, it was confirmed that the poorly water-soluble materials (1b) blended as ingredients in the solid compositions (Examples 39 to 50) produced by combining polysaccharides (molecular weight 972 or more) (3) and HPMC (2) were all highly amorphous. Furthermore, the amorphous nature of the poorly water-soluble materials was stable for a long period of time. As for astaxanthin, the combination of HPMC and polysorbate maintained an amorphous state for a long period of time, but the residual rate in the sample was extremely low at 46%, and a change in color was observed after storage (Comparative Example 6). Astaxanthin is also highly valuable as a food coloring, so the astaxanthin composition of the present invention (Example 50) was superior in that it did not change color after storage and had high stability within the composition.
[0133] Test Example 5 (Comparative Examples 7 and 8) (1) Preparation of CUR-containing formulations using organic solvent method Each component was added to 300 mL of 70% ethanol water in the ratio shown in Table 14, and stirred while heating to 80°C until the CUR raw material was dissolved. While maintaining the mixture at 80°C, the mixture was dried under reduced pressure using an evaporator (rotary evaporator N-1300, EYELA Co., Ltd.) to remove the solvent. The resulting dried product was ground with a mortar and pestle and subjected to XRD analysis under the above conditions. [Table 14]
[0134] (2) Preparation of amorphous preparations by heating and kneading (melting) CUR alone Only the CUR raw material was heated and kneaded using an extruder until it was molten, and the amorphous material was cooled and then pulverized using a mortar and pestle. Formulations were prepared at room temperature with the addition of HPMC and / or dextrin shown in Table 15 as excipients. [Table 15]
[0135] (3) XRD analysis of CUR-containing formulations The results of XRD analysis of the CUR-containing preparations prepared in (1) and (2) above are shown in Figures 5 and 6. In both preparations of Comparative Examples 7 and 8 produced by the organic solvent method, the remaining crystalline structure was observed immediately after production (initial stage), and the desired amorphous state was not formed (Figure 5). In addition, when curcumin was melted alone and made amorphous, the XRD analysis value decreased according to the amount of polysaccharide added after amorphization (Figure 6). However, even when about three times the amount of polysaccharide as curcumin was added, the XRD analysis value immediately after preparation was only 4.9% or 4.8% (Comparative Examples 9 and 10). Therefore, in order to further increase the degree of amorphousness, it is considered important to add the polysaccharide (3) specified in the present invention during heating and kneading.
[0136] Test Example 6 A powdered solid composition (Example 51) was prepared using the same recipe and manufacturing conditions as Example 1' prepared in Test Example 1, except that the heating time was approximately 2 minutes. The XRD analysis value of the composition was 0%, the same as Example 1' (Figure 1-1). Next, the solid composition (Example 51) was powder-mixed with the crystalline curcumin raw material (Table 3) in the ratio shown in Table 16, and the resulting powder mixtures (Test Samples 1 to 5) were subjected to an XRD analyzer under the conditions described above, and the XRD analysis values were obtained from the chart. Table 16 also shows the total CUR content (%) contained in each powder mixture (Test Samples 1 to 5) and the crystalline CUR content (%) in the total CUR content (100%). [Table 16]
[0137] Figure 7-1 shows the XRD analysis charts of test samples 1 to 5 and the XRD analysis values calculated from them. Figure 7-2 shows a plot of the crystalline CUR content (in brackets in column (B)) (column (D) of Table 16) in the (C) powder mixture on the X-axis and the XRD analysis values on the Y-axis for each test sample. As shown in Figure 7-2, it was confirmed that there is a good correlation between the crystalline CUR content (%) in the (C) powder mixture and the XRD analysis values {(S2) / ((S1)+(S2))×100(%)} (R 2 =0.9984). From this, it is believed that by creating a calibration curve as described above and using the XRD analysis values of the measurement sample, it is possible to determine the crystalline proportion (or amorphous proportion) of the water-insoluble material in the measurement sample.
[0138] In addition, for each test sample, the content (%) of crystalline CUR (in parentheses in column (B)) in the total curcumin content (the sum of the contents in parentheses in columns (A) and (B)) (column (E) of Table 16) is plotted on the X-axis, and the XRD analysis values are plotted on the Y-axis. As shown in Figure 7-3, it was confirmed that there is a good correlation between the content (%) of crystalline CUR in the total CUR content and the XRD analysis values (R 2 =0.9907). From this, it is believed that by creating a calibration curve as described above and using the XRD analysis values of the measurement sample, it is possible to determine the crystalline proportion (or amorphous proportion) of the water-insoluble material in the measurement sample.
Claims
1. An amorphous poorly water-soluble material (1a), Hydroxypropyl methylcellulose (2), and A solid composition containing a polysaccharide having five or more sugars other than hydroxypropyl methylcellulose (3), The amorphous water-insoluble material (1a) is at least one selected from the group consisting of luteolin, hesperetin, naringenin, quercetin, silymarin, resveratrol, and astaxanthin; A solid composition, wherein the XRD analysis of said solid composition is 4.0% or less: Here, the XRD analysis value is, in a chart obtained by analyzing the solid composition with a powder X-ray diffractometer, the area of the halo peak in the range of 2θ = 5 to 60 ° is (S1), and the area of the sharp peak originating from the crystalline water-insoluble material (1b) beyond the halo peak is (S2). This value is calculated using the formula: {(S2) / ((S1)+(S2))}×100(%).
2. 2. The solid composition according to claim 1, wherein the polysaccharide (3) is one or more selected from the group consisting of gum arabic, hydroxypropyl cellulose (HPC), gum ghatti, low molecular weight gum ghatti, modified starch, locust bean gum, guar gum, alginic acid or a salt thereof, carrageenan, pectin, xanthan gum, pullulan, microcrystalline cellulose, fermented cellulose, methylcellulose, carboxymethylcellulose, dextrin, cyclodextrin, soybean polysaccharides, agar, tamarind seed gum, hydrolyzed guar gum, karaya gum, tara gum, welan gum, and gellan gum.
3. 3. The solid composition according to claim 1 or 2, wherein the polysaccharide (3) is a combination of hydroxypropyl cellulose and another polysaccharide (3).
4. A solid composition comprising the solid composition according to any one of claims 1 to 3, and a crystalline poorly water-soluble material (1b) corresponding to the amorphous poorly water-soluble material (1a) added thereto.
5. An oral composition comprising the solid composition according to any one of claims 1 to 4.
6. A pharmaceutical product, a quasi-drug product, a food or beverage product, an oral care product, or a cosmetic product, comprising the solid composition according to any one of claims 1 to 4 together with an additive for the pharmaceutical product, the quasi-drug product, the food or beverage product, the oral care product, or the cosmetic product.
7. A crystalline, poorly water-soluble material (1b); Hydroxypropyl methylcellulose (2), and A method for producing the solid composition according to any one of claims 1 to 4, comprising the step of heating and kneading (3) a polysaccharide having five or more sugars other than hydroxypropyl methylcellulose, by using a kneader to melt the polysaccharide, The above-mentioned production method, wherein the crystalline poorly water-soluble material (1b) is one or more selected from the group consisting of luteolin, hesperetin, naringenin, quercetin, silymarin, resveratrol, and astaxanthin.
8. The method according to claim 7, wherein the heat-kneading step is carried out at a temperature equal to or higher than the glass transition temperature Tg of the crystalline poorly water-soluble material (1b).
9. The method according to claim 7 or 8, further comprising at least one step selected from the group consisting of a cooling step, a crushing or pulverizing step, a drying step, a granulating step, and a sizing step.
Citation Information
Patent Citations
Production of solid dispersed form for poorly soluble medicinal substance
JP1993262642A
Polylactic acid resin composition and molded article
JP2007002243A
Method for producing solid dispersion containing difficult-to-dissolve polyphenol
JP2016049105A
Oral composition
JP2018078860A
Production method of formulation for making amorphous material
JP2019123700A